Inhibition of oestrogen biosynthesis induces mild anxiety in C57BL/6J ovariectomized female mice - Meng, Fan-Tao (Neurosci Bull, 2011)
OBJECTIVE: Letrozole, a next-generation aromatase inhibitor, has become a favored drug for the treatment of breast cancer in postmenopausal women. Although letrozole is generally well tolerated, its adverse effects on the central nervous system have been reported. The present study aimed to assess the behavioural outcomes of letrozole administration in mice to determine its side effects. METHODS: C57BL/6J female ovariectomized mice received administration of letrozole (2.5 mg/kg per day) or vehicle by gavage for 3 weeks. Behavioural tasks were used to assess anxiety, depression, as well as learning and memory in mice. RESULTS: Letrozole-treated mice showed an increased latency to enter the inner area of the chamber on the third day of the open field test, and traveled a shorter distance in the open arms of the elevated plus maze. No significant difference was found in the light-dark box or forced swimming task between letrozole-treated and vehicle-treated mice. Besides, letrozole did not change the spontaneous alternation behaviour of mice in the Y-maze. In the Morris water maze, mice administered with letrozole exhibited an improvement in spatial learning and memory compared with the vehicle-treated mice. CONCLUSION: Our results indicate that the inhibition of oestrogen biosynthesis results in mild anxious behaviour, which may be a consideration in the treatment of breast cancer in postmenopausal women using aromatase inhibitors.